Mitigating Property Conflicts in Benin City: The Role of Estate Managers - David, Adekunle; Adediji, Adeniyi Anthony (Faculty of Natural and Applied Sciences Journal of Basic and Environmental Research, 2025)
This paper discusses how the estate managers can reduce conflicts related to property in the city of Benin, Edo State. Due to the swift urbanisation and the conflict between traditional and legal land tenure systems, the ownership, inheritance, landlord-tenant relationships and boundary boundaries disputes are becoming more prevalent within the city. The study employs a descriptive survey of all the estate managers, landlords, and tenants to determine the key triggers of property disputes and assess how the estate managers had dealt with them using their strategies. Research results indicate that mediation, adequate documentation, and cooperation with traditional authorities are the most popular and efficient conflict-resolution scales. Nevertheless, systemic limitations, such as poor land records, ineffective enforcement of the rules and rules, as well as political and traditional interference curtail the effectiveness of these interventions. Based on the Conflict Transformation Theory, the research claims that the estate managers should not be merely regarded as the mediators but as the strategic players who can impact structural changes in the land governance. This paper has determined that sustainable mitigation of conflicts in the real estate sector in Benin City requires strengthening of professionalism, availability of correct land information, and institutions collaboration.